2011
DOI: 10.1073/pnas.1018360108
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response curve slope is a missing dimension in the analysis of HIV-1 drug resistance

Abstract: HIV-1 drug resistance is a major clinical problem. Resistance is evaluated using in vitro assays measuring the fold change in IC 50 caused by resistance mutations. Antiretroviral drugs are used at concentrations above IC 50 , however, and inhibition at clinical concentrations can only be predicted from IC 50 if the shape of the dose-response curve is also known. Curve shape is influenced by cooperative interactions and is described mathematically by the slope parameter or Hill coefficient (m). Implicit in curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
133
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(142 citation statements)
references
References 58 publications
9
133
0
Order By: Relevance
“…1B, Methods, and SI Appendix). The antiviral activity of a drug can be expressed as the instantaneous inhibitory potential (IIP) (13)(14)(15)(16)(17)(18):…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1B, Methods, and SI Appendix). The antiviral activity of a drug can be expressed as the instantaneous inhibitory potential (IIP) (13)(14)(15)(16)(17)(18):…”
Section: Resultsmentioning
confidence: 99%
“…This system supports efficient replication of genotype 1 HCV, and thus enables one to measure the intrinsic antiviral effects of any drug combination and at any concentration of the component drugs in a highly sensitive manner and with high throughput. The experimental data were analyzed by calculating the IIP, which is the log reduction in HCV replication caused by drugs singly and in combination at a particular concentration (13)(14)(15)(16)(17)(18). From the calculated IIP of 15 anti-HCV drugs, we found that IFN-α and the NI SOF had the largest potential to inhibit viral replication events.…”
Section: Discussionmentioning
confidence: 99%
“…As this can significantly vary between individuals due to immunity and quasispecies differences, the attributed R 0 is sampled from random distributions, which are reported for patients in the acute (primary infection, higher viral growth rate) and chronic (a few months after primary infection) phases 11, 12. For the resistant strain, growth is hampered by a nonzero fitness cost ( s ), which value depends on the considered mutation, and is reported for multiple strains in Sampah et al 13. A newly infected cell starts producing new virions after an eclipse period of 1 day ( τ ) and for a median period of 1 day ( d y ) 14, 15.…”
Section: Methodsmentioning
confidence: 99%
“…The former is taken from a random distribution since significant quasispecies differences in IC 50 are commonly reported 17. For the treatments investigated herein, these parameters were obtained from the product monographs3, 18, 19, 20 and from results of in vitro experimentations 1, 13. For the resistant strain, the model uses the fold‐change in IC 50 ( ρ ) and the correction factor for the Hill coefficient ( σ ) 4, 13.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation